UAS-SfM as a Cost-Effective Tool for Coastal Monitoring and Management - Lazogiannis, K.; Vassilakis, Emm; Poulos, S.; Kotsopoulos, S; Alexopoulos, J.; Alamanis, N; Papageorgiou, G. (1st International Scientific Conference on Design and Management of Port Coastal and Offshore Works, 2019)
Coastal zone monitoring is essential in order to understand their evolution and incorporate sustainable coastal management practices. Frequent data collection is essential but often surveys can be costly and time-consuming. Several costly and time-consuming tools and techniques have been developed during the last few years for change detection and monitoring, allowing for both qualitative and quantitative analysis. In this study we present the ability of an off-the-shelf Unmanned Aerial Systems (UAS) coupled with Structure-from-Motion (SfM) photogrammetry to map and measure coastal features (e.g. shorelines). The UAS surveys taken place over three campaigns during Autumn 2017 (November), Spring 2018 (March) and Autumn 2018 (October) in Pinios river deltaic coast. The demonstrated UAS-SfM methodology produced remote sensing data with great spatial resolution which could be used to visually identify important parameters for coastal research and management at a fraction of the cost of other available techniques and. Even an off-the-shelf UAS is suitable for repeat surveys to assess spatial and temporal changes at small spatial extents and to better comprehend how these may be related with site-specific natural processes along the coast.